Didactic prototype of student modern training: aspect of educational robotic complex realization - O. Baklanov, Igor (2019)
The relevance of the study is due to the changed trends in University students’ training, suggesting an effective solution to educational problems with the help of digital means, among which a special place takes the robotic complex. In this regard, the article for the first time, as an independent scientific direction, attempts to substantiate the theoretical and methodological approach to the use of educational robotic complex as a didactic prototype of modern student training. During the implementation of pedagogical modeling - the leading method of research, educational robotic complex is justified as a methodological basis for the didactic prototype of student training. Taking into account the new trends in the transformation of student training, the article reveals the phenomenology of the educational robotic complex. Based on its results the study establishes the pedagogical terms of the educational robotic complex’s realization; substantiates algorithm of didactic designing of a prototype educational robotic systems and proves its effectiveness in educational process of the University. The article focuses materials on providing methodological assistance to University teachers and students in the development and use of educational robotic complex in the educational process of the University. It gives recommendations for teachers, methodologists, University managers and students.